NGS-based methylation profiling differentiates TCF3-HLF and TCF3-PBX1 positive B-cell acute lymphoblastic leukemia. (February 2018) - Kachroo, Priyadarshini; Szymczak, Silke; Heinsen, Femke-Anouska; Forster, Michael; Bethune, Jörn; Hemmrich-Stanisak, Georg; Baker, Lewis; Schrappe, Martin; Stanulla, Martin; Franke, Andre
Aim: To determine whether methylation differences between mostly fatal TCF3-HLF and curable TCF3-PBX1 pediatric acute lymphoblastic leukemia subtypes can be associated with differential gene expression and remission.Materials & methods: Five (extremely rare) TCF3-HLF versus five (very similar) TCF3-PBX1 patients were sampled before and after remission and analyzed using reduced representation bisulfite sequencing and RNA-sequencing.Results: We identified 7000 differentially methylated CpG sites between subtypes, of which 78% had lower methylation levels in TCF3-HLF. Gene expression was negatively correlated with CpG sites in 23 genes. KBTBD11 clearly differed in methylation and expression between subtypes and before and after remission in TCF3-HLF samples.Conclusion: KBTBD11 hypomethylation may be a promising potential target for further experimental validation especially for the TCF3-HLF subtype.